Strategi Dan Proses Pembelajaran PAI Di SLB A Yaketunis Yogyakarta - Naila Nur ‘Azizah; Miftah Aziza; Zulfiham Hadyan Nadhil; Difa’ul Husna (Pusat Riset dan Inovasi Nasional, 2024)
Children with special needs are those who have special differences in their types and characteristics, which differentiate them from children in general. They need special education and services to help develop their potential. Therefore, the author took the initiative to conduct observations and interviews at an inclusive school in order to obtain accurate information according to the situation in the field. The approach used involves literature searches and direct interviews to explore relevant topics. SLB A Yaketunis Yogyakarta is a school that provides special education programs for blind children. In the learning process, the focus is on the sense of hearing and changing the learning material into song lyrics to make it easier for students to understand the learning material.